Diseño, implementación y evaluación de un sistema de riego por aspersión utilizando un equipo motobomba en la Finca San José - Jiménez Cumbicus, Robinson Andrés (2019)
In the San José farm belonging to the April 27 Parish of the Espíndola canton, Loja Province, the design, implementation and evaluation of the sprinkler irrigation system was carried out using a drive pump in an area of 0.26 ha. In the design, the physical evaluation of the soil is necessary, where undisturbed samples were taken with the help of Köppeckycylinders of 100 cm, for the determination of field capacity at 1/3 and 1/10 of atm, wilting point permanent, apparent density, and texture. Effective root depth was calculated by sampling in situ of corn plants; and, the infiltration rate was obtained by the infiltrometer cylinders. In the agronomic design, the irrigation needs of the corn crop were calculated, where the indirect Penman Monteith method was used to obtain the ETo of the Cariamanga, Amaluza and Nambacola weather stations, by means of liner regression based on the altitude in the ArcGis program determined the ETo of the study area; The kc curve was obtained from the research carried out by Ureña (2016), resulting in crop evapotranspiration. It was determined, the sheet, times and frequencies of irrigation. In the hydraulic design, the hydraulic network, main, secondary or multiple and lateral, was calculated with nominal diameters of 2”, 2” and 1” respectively, using the Hazen- Williams formula, in addition the Christiansen coefficient was calculated for multi-outlet pipes. The 4.8 HP Honda WH20XT motor pump was selected, with a design flow of 3.66 l/s and a total dynamic load of 33.94 m. After installing the irrigation system, the evaluation was carried out using the Christiansen (UC) uniformity coefficient, which was 91%. Keywords: sprinkler irrigation, agronomic design, hydraulic design, evaluation, Christiansen uniformity coefficient.